2018
DOI: 10.1073/pnas.1803908115
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic regions and events of isolation and diversification of the endemic biota of the tropical Andes

Abstract: Understanding the spatial and temporal evolution of biota in the tropical Andes is a major challenge, given the region's topographic complexity and high beta diversity. We used a network approach to find biogeographic regions (bioregions) based on high-resolution species distribution models for 151 endemic bird taxa. Then, we used dated molecular phylogenies of 14 genera to reconstruct the area history through a sequence of allopatric speciation processes. We identified 15 biogeographical regions and found 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
204
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(224 citation statements)
references
References 53 publications
10
204
0
10
Order By: Relevance
“…Several insightful schematic representations of Pleistocene diversification models in the Neotropics have been developed in recent years (Flantua & Hooghiemstra, ; Hazzi, Moreno, Ortiz‐Movliav, & Palacio, ; Ramírez‐Barahona & Eguiarte, ; Rull, ). Phylogeographical and phylogenetic synthesis work within and among páramo taxa is currently still largely lacking (see for instance Yu et al., for the Qinghai‐Tibet Plateau), inhibiting the direct testing of these models.…”
Section: Discussionmentioning
confidence: 99%
“…Several insightful schematic representations of Pleistocene diversification models in the Neotropics have been developed in recent years (Flantua & Hooghiemstra, ; Hazzi, Moreno, Ortiz‐Movliav, & Palacio, ; Ramírez‐Barahona & Eguiarte, ; Rull, ). Phylogeographical and phylogenetic synthesis work within and among páramo taxa is currently still largely lacking (see for instance Yu et al., for the Qinghai‐Tibet Plateau), inhibiting the direct testing of these models.…”
Section: Discussionmentioning
confidence: 99%
“…Antonelli et al (), for example, found extensive rates of biotic interchange across different taxonomic groups and between major Neotropical regions – Amazonia being the primary source of diversity. Similarly, Hazzi et al () found that patterns of spatial and temporal evolution in birds from the Tropical Andes were explained by a combination of vicariance driven by mountain uplift and downslope dispersal events using river valley habitats. We complement these findings by identifying a fine‐scale case occurring in an ecologically distinct group of animals (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…His 22‐month‐long expedition along the northern Andes in the early 19th century certainly constituted a pivotal time for the establishment of his revolutionary ideas about the natural world. Although great advances have been made in how biodiversity is generated in the Neotropics, an understanding of the origin and maintenance of Andean diversity is still incomplete (Hazzi, Moreno, Ortiz‐Movliav, & Palacio, ). In South America, the uplift of the Andes mountain range undoubtedly played an important role in the diversification of several taxonomic groups (Antonelli et al, ; Esquerré, Brennan, Catullo, Torres‐Pérez, & Keogh, ; Hoorn et al, ; Lagomarsino, Condamine, Antonelli, Mulch, & Davis, ).…”
Section: Introductionmentioning
confidence: 99%
“…For further relevant readings, see Caley et al [7], Hazzi et al [8], Hildebrand et al [9], Maier et al [10], Nogués-Bravo et al [11], Nolan et al [12], Scerri et al [13], and Taylor et al [14].…”
Section: Other Relevant Papersmentioning
confidence: 99%